Drug resistance among Escherichia coli strains isolated from cerebrospinal fluid. - Gross, R. J. (Cambridge University Press, 1983)
One hundred and thirty-one strains of Escherichia coli isolated from the cerebrospinal fluid of patients in the United Kingdom were tested for resistance to 13 antimicrobial drugs. Sixty-four strains (49%) were resistant to one or more drugs and 44 (34%) were resistant to three or more drugs. Resistance to ampicillin, sulphonamides, streptomycin and tetracycline occurred most frequently.